Pendugaan Parameter Genetik Semai Nyawai (Ficus Variegata Blume) Asal Pulau Lombok - Liliek Haryjanto; Prastyono (Jurnal Penelitian Kehutanan Wallacea, 2014)
Genetic parameters were estimated for height and diameter characteristic of Ficus variegata Blume seedlings planted in the nursery of The Centre for Forest Biotechnology and Tree Improvement, Yogyakarta at 8 months of age. The trial involved seedlings from several mother trees (family) originated from Lombok Island. The trial was arranged in a Randomized Complete Block Design (RCBD) which comprised of 17 families as treatment, 3 replications and each replication comprised 10 seedlings. Analysis of varians showed that height and diameter were significantly different between families. Family heritabilities for height and diameter characteristic were 0.98 and 0.91 respectively, while genetic correlation between the two characteristics were 0.7. This information is very important for future genetic improvement of the species.